Using optical fibers (OF) to control the stress-strain state of steel structures subject to fatigue failure - V. V. Yugay (Croatian Metallurgical Society, 2022)
The article presents the results related to developing and practical testing the method of monitoring the stress strain state of steel structures of mine hoisting machines. Certain positive properties of optical fibers make it possible to use them for measuring the stress-strain state of steel structures. An optical fiber of the ITU-T G.652.D standard is used as a sensor. The analysis and review of the current state of development of fiber-optic conductors is performed. The proposed method of non-destructive testing the stress-strain state of metal structures is capable of providing continuous measurements in real time. The proposed method is universal and suitable for monitoring the stress-strain state of any metal structures subject to fatigue failure.